Job satisfaction moderate the effect of integrity, work experience, and organizational commitment on audit quality - Sadiah, Imas Siti; Rasmini, Ni Ketut; Yasa, Gerianta Wirawan; Erawati, Ni Made Adi (International research journal of management, IT and social sciences, 2023)
This study aims to provide a more comprehensive view of the influence of integrity, work experience, and organizational commitment on audit quality moderated by job satisfaction. A quantitative associative approach was used in this study with a total sample of 59 people, namely all auditors at the Inspectorate of the Province of Bali. Data collection techniques used questionnaires which were analyzed with structural equation modelling with SmartPLS3.0 and for descriptive statistical testing using SPSS 25. The findings in this study are integrity, work experience, and organizational commitment have a positive effect on audit quality. Regarding moderating variables, job satisfaction strengthens the positive effect of integrity and work experience on audit quality, and job satisfaction does not moderate the effect of organizational commitment on audit quality. The conclusion from this study is that the higher the integrity, work experience, and organizational commitment, the auditor tends to be responsible for carrying out inspection duties to obtain good audit quality. Job satisfaction is an additional benefit to increase the integrity and work experience of the auditor in carrying out audit duties to realize good audit quality.